An Investigation of the Transformation Process from Manual to E-Recruitment in Tanzania Public Service - Saad, Azah; Itika, Josephat (Journal of Public Policy and Administration, 2024)
Purpose: The innovation of e-recruitment was to embrace the flow of recruitment and selection of young people in Tanzania public service. Currently, e-recruitment has not yet achieved the intended objectives. As a result, the wellbeing of the country human capital is being compromised. The extant studies have not examined the effectiveness of e-recruitment transformation process. In line with the existing gap, investigating the transformation process from manual to e-recruitment in Tanzania Public Services Recruitment Secretariat remains is the focus of this study. Specifically, the study examined why e-recruitment was an alternative to the manual recruitment, the regulatory frameworks governing e-recruitment, e-recruitment implementation strategies, and processes and finding out how the management of forces for change may explain the reasons why e-recruitment does not meet the intended objectives. Methodology: With the sample size of 25 respondents, five respondents were purposively interviewed and nine responded to questionnaires, and the remaining 16 respondent were conveniently distributed into two FGDs basing on their willingness, availability, willingness, and accessibility. Qualitative data were analysed using thematic and content analysis. Findings: The findings revealed that the adoption of e-recruitment was due to challenges facing manual recruitment such as diseases, unfairness, insecurity of applicants' information, the cost of running the recruitment process and time. The e-government Act of 2019, e-government regulations of 2020 and the PSRS Rules of operations of 2021 were identified as the regulatory frameworks governing e-recruitment. The PSRS uses both human capital sand technological strategies in facilitating e-recruitment. Finally, the inability of using e-recruitment system, limited reach, budget constraints, and inadequate system integration were the reasons why e-recruitment does not meet the intended objectives. Unique Contribution to Theory, Practice and Policy: The study recommend for the government to ensure integration and interoperability of between e-recruitment system and other government systems for accurate data sharing and verification purposes.